Cutaneous Autonomic Pilomotor Testing to Unveil the Role of Neuropathy Progression in Early Parkinson’s Disease (CAPTURE PD): Protocol for a Multicenter Study - Siepmann, Timo; Pintér, Alexandra; Buchmann, Sylvia J.; Stibal, Leonie; Arndt, Martin; Kubasch, Anne Sophie; Kubasch, Marie Luise; Penzlin, Ana Isabel; Frenz, Elka; Zago, Wagner; Horváth, Tamás; Szatmári, Szabolcs; et al. (Frontiers in Neurology, 2017)
Background: In Parkinson's disease (PD), alpha-synuclein accumulation in cutaneous autonomic pilomotor and sudomotor nerve fibers has been linked to autonomic nervous system disturbances even in the early stages of the disease. This study aims to assess the association between alpha-synuclein mediated structural autonomic nerve fiber damage and function in PD, elucidate the role of neuropathy progression during the early disease stages, and test reproducibility and external validity of pilomotor function assessment using quantitative pilomotor axon-reflex test (QPART) and sudomotor function via quantitative direct and indirect test of sudomotor function (QDIRT). Methods/Design: A prospective controlled study will be conducted at four study sites in Europe and the United States. 52 male and female patients with idiopathic PD (Hoehn & Yahr 1-2) and 52 age- and sex-matched healthy controls will be recruited. Axon-reflex mediated pilomotor erection will be induced by iontophoresis of phenylephrine on the dorsal forearm. Silicone impressions of the response will be obtained, scanned and quantified for pilomotor muscle impressions by number, impression size and area of axon-reflex spread. Axon-reflex mediated sweating following acetylcholine iontophoresis will be quantified for number and size of droplets and axon-reflex spread. Sympathetic skin responses, autonomic and motor symptoms will be evaluated. Tests will be performed at baseline, after 2 weeks, 1 year, 2 years and 3 years. Skin biopsies will be obtained at baseline and after 3 years and will be analyzed for nerve fiber density and alpha-synuclein accumulation. Discussion: We anticipate that progression of autonomic nerve dysfunction assessed via pilomotor and sudomotor axon-reflex tests is related to progression of autonomic symptom severity and alpha-synuclein deposition. Potential applications of the techniques include interventional studies evaluating disease-modifying approaches and clinical assessment of autonomic dysfunction in patients with Parkinson’s disease.